2014
DOI: 10.1177/1071100714551021
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal and Activity-Related Factors Associated With Plantar Heel Pain

Abstract: Level III, comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 50 publications
1
41
2
3
Order By: Relevance
“…The intrinsic and extrinsic foot muscles play an important role in maintaining the arches of the foot while walking [30]. The strengthening exercise program for these muscles was expected to have better improvements in pain and gait parameters than the stretching exercise program [19,35]. However, the present study found the same effect from both programs on pain and gait.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…The intrinsic and extrinsic foot muscles play an important role in maintaining the arches of the foot while walking [30]. The strengthening exercise program for these muscles was expected to have better improvements in pain and gait parameters than the stretching exercise program [19,35]. However, the present study found the same effect from both programs on pain and gait.…”
Section: Discussioncontrasting
confidence: 51%
“…In addition, weakness of the tibialis posterior muscle was also reported in previous studies [4,20]. Weakness of the intrinsic and extrinsic muscles of the foot may result in the recurrent symptoms of PF due to improper functioning of the muscle and joint positioning during walking [4,13,19]. Rathleff et al [21] in 2014 reported that daily heel-raising exercises have superior effectiveness at 3 months than plantar-specific stretching.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…The plantar fascia also prevents this deflection (8) and undergoes strain as the arch deflects downward. Weakness of the intrinsic muscles of the arch can lead to a greater deflection and/or velocity of deflection of the arch, placing increased strain on the plantar fascia (3,9). With the repetitive nature of walking (over 2000 steps per mile), this can easily accumulate into an overuse injury and may explain, in part, the high lifetime incidence (10% of population) of plantar fasciitis reported today (10).…”
mentioning
confidence: 99%